2007
DOI: 10.1073/pnas.0700923104
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin directly regulates Islet1 expression in cardiovascular progenitors and is required for multiple aspects of cardiogenesis

Abstract: Recent studies have demonstrated that the LIM homeodomain transcription factor Islet1 (Isl1) marks pluripotent cardiovascular progenitor cells and is required for proliferation, survival, and migration of recently defined second heart field progenitors. Factors that are upstream of Isl1 in cardiovascular progenitors have not yet been defined. Here we demonstrate that ␤-catenin is required for Isl1 expression in cardiac progenitors, directly regulating the Isl1 promoter. Ablation of ␤-catenin in Isl1-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
202
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(220 citation statements)
references
References 45 publications
17
202
0
1
Order By: Relevance
“…In contrast, SHF specification was severely disturbed, resulting in a lack of cardiac looping and proper outflow tract and right ventricle formation. It was recently shown that defects in right ventricle and outflow tract formation are also observed when competence to Wnt signaling was removed during and after SHF specification (48,49). Our results using both loss-and gain-of-function mutations of ␤-catenin suggest that it may be the amount of Wnt/␤-catenin signaling that is important for early cardiogenesis.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, SHF specification was severely disturbed, resulting in a lack of cardiac looping and proper outflow tract and right ventricle formation. It was recently shown that defects in right ventricle and outflow tract formation are also observed when competence to Wnt signaling was removed during and after SHF specification (48,49). Our results using both loss-and gain-of-function mutations of ␤-catenin suggest that it may be the amount of Wnt/␤-catenin signaling that is important for early cardiogenesis.…”
Section: Discussionmentioning
confidence: 48%
“…The tissue-specific downregulation of ␤-catenin in the SHF using different Cre mouse lines leads to a reduction of Isl1-positive cells in comparison to wild-type mice as well as a loss of the SHF-derived OFT and right ventricle. 79 -83 Moreover, it has been shown by chromatin immunoprecipitation experiments that ␤-catenin is directly binding and positively regulating the Isl1 promotor 83 whereas others reported a negative regulation. 47 Also, FGF ligands were supposed to be downstream of ␤-catenin signaling.…”
Section: Cardiac Specification: Positive Influence Of Noncanonical Wnmentioning
confidence: 99%
“…Missense mutation of low-density lipoprotein receptor-related protein 6 in humans, which encodes a coreceptor of Wnt results in early coronary artery disease and multiple cardiovascular risk factors (51). In addition, a TCF/ Lef-LacZ reporter of ␤-catenin transcriptional activity has identified both the proepicardium and the epicardium as active targets of Wnt-mediated transcriptional activity (27). Here, we have demonstrated progenitor differentiation into the smooth muscle lineage is largely impaired in the epiBC-KO epicardium.…”
Section: Impaired Development Of Epdcs and Myocardial Growth Defectsmentioning
confidence: 99%
“…19). In the heart, Wnt signaling plays a pivotal role in cardiomyocyte specification, and both activation and inhibition of Wnt signaling affect the formation of the cardiomyocyte compartment (20-27), suggesting that the muscular component of the heart depends on the cellular context in which Wnt stimulation occurs (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation